New Record of a Rare and Little known Aquatic Plant Nymphoides aurantiaca (Dalzell) Kuntze from Jalpaiguri District of West Bengal, India - Dey, Manas; Mazumder, Mallika; Kumar Sarkar, Anup (Indian Forester, 2019)
No Abstract.